Study guide for Ralph, Lerner, Meacham, Wood, Hull, and Burns "World civilizations" volume 2 - Allen, J. Michael, 1956- (New York ; London : W. W. Norton, 1997)
India, East Asia, and Africa during the early-modern era c. (1500-1800). The economy and society of early-modern Europe. The age of absolutism (1660-1789). The scientific revolution and enlightenment. Overseas exploration in the 15th and 16th centuries and Europe in 1560...
Keywords: History; Civilization; Civilization -- History